Équivoque litteraire et contrat de lecture - Alain Trouvé (Carnets)
Equivocation, which derives from its opposite “univocity”, is first of all a matter of genre and reading contract. When authorial intention, which is necessary to the contract, is blurred, equivocation can be described as a drifting course of action. Interpretation is also affected: with the author’s complicity or by taking his distance with it, the reader aims to reduce equivocation into univocity, unless he is bent on doing exactly the opposite. As far as the construction of meaning is concerned, fiction, particularly novelistic fiction, is a choice nursing ground for equivocation.